Answer:
C. x = -12 and x = 2
Step-by-step explanation:
-x²-10x+24=0 Original equation
x²+10x-24=0 Divide everything by -1
(x+12)(x-2)=0 Factor it out
x=-12,2 Solve so that the inside of the parentheses equals 0
Answer:
StartFraction 6 Over 5 x Superscript 10 Baseline EndFraction
Step-by-step explanation:
Apparently you want to simplify ...
![\sqrt{\dfrac{72x^{16}}{50x^{36}}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cdfrac%7B72x%5E%7B16%7D%7D%7B50x%5E%7B36%7D%7D%7D)
The applicable rules of exponents are ...
(a^b)(a^c) = a^(b+c)
1/a^b = a^-b
(a^b)^c = a^(bc)
__
So the expression simplifies as ...
![\sqrt{\dfrac{72x^{16}}{50x^{36}}}=\sqrt{\dfrac{36}{25x^{36-16}}}=\sqrt{\dfrac{36}{25x^{20}}}\\\\\sqrt{\left(\dfrac{6}{5x^{10}}\right)^2}=\boxed{\dfrac{6}{5x^{10}}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cdfrac%7B72x%5E%7B16%7D%7D%7B50x%5E%7B36%7D%7D%7D%3D%5Csqrt%7B%5Cdfrac%7B36%7D%7B25x%5E%7B36-16%7D%7D%7D%3D%5Csqrt%7B%5Cdfrac%7B36%7D%7B25x%5E%7B20%7D%7D%7D%5C%5C%5C%5C%5Csqrt%7B%5Cleft%28%5Cdfrac%7B6%7D%7B5x%5E%7B10%7D%7D%5Cright%29%5E2%7D%3D%5Cboxed%7B%5Cdfrac%7B6%7D%7B5x%5E%7B10%7D%7D%7D)
The intercept can be found when all other variables are equated to zero.
x-intercept when y = 0 and z = 0: 8x + 6*0 + 3*0 = 24 gives x = 3
y-intercept when x = 0 and z = 0: 8*0 + 6y + 3*0 = 24 gives y = 4
z-intercept when x = 0 and y = 0: 8*0 + 6*0 + 3z = 24 gives z = 8
The intercepts are (3, 0, 0), (0, 4, 0), and (0, 0, 8).